2012
DOI: 10.1186/1472-6807-12-21
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the binding of BACE-1 inhibitors using comparative binding energy analysis (COMBINE)

Abstract: BackgroundThe inhibition of the activity of β-secretase (BACE-1) is a potentially important approach for the treatment of Alzheimer disease. To explore the mechanism of inhibition, we describe the use of 46 X-ray crystallographic BACE-1/inhibitor complexes to derive quantitative structure-activity relationship (QSAR) models. The inhibitors were aligned by superimposing 46 X-ray crystallographic BACE-1/inhibitor complexes, and gCOMBINE software was used to perform COMparative BINding Energy (COMBINE) analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 84 publications
3
18
0
Order By: Relevance
“…These results show compound 77 could adequately occupy the binding pocket of BACE-1 and are better to bind with BACE-1. And it is in agreement with the result obtained by Shu Liu et al that key residues involved in binding the ligand are analyzed by the COMBINE method (Liu et al, 2012). And the above analysis showed that the van der Waals and electrostatic interactions are important for the binding affinity of compound 77 and 52 to BACE-1 and compound 77 could form stronger interactions with BACE-1 than compound 52.…”
Section: Binding Free Energy Calculationssupporting
confidence: 86%
See 1 more Smart Citation
“…These results show compound 77 could adequately occupy the binding pocket of BACE-1 and are better to bind with BACE-1. And it is in agreement with the result obtained by Shu Liu et al that key residues involved in binding the ligand are analyzed by the COMBINE method (Liu et al, 2012). And the above analysis showed that the van der Waals and electrostatic interactions are important for the binding affinity of compound 77 and 52 to BACE-1 and compound 77 could form stronger interactions with BACE-1 than compound 52.…”
Section: Binding Free Energy Calculationssupporting
confidence: 86%
“…Thus, there is interesting to use more efficient and low-costs in silico modeling approaches, such as quantitative structure-activity relationship (QSAR), pharmacophore modeling, virtual screening and molecular dynamics (MD) simulations, to predict the biological activities of BACE-1 (Al-Nadaf et al, 2010;Ghemtio and Muzet, 2013;Huang et al, 2013;John et al, 2011;Kacker et al, 2012;Liu et al, 2012;Pandey et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The loop 8–14 (also known as 10s) can be found in at least two conformations (denoted in and out in Fig 3), and the transition between these conformations seems to be induced by the specific structural motifs of the ligand [5153], such as the benzene ring in the inhibitor found in 2P4J. Even though the conformational differences in the loops 154–169 and 307–318 are less apparent in Fig 3, the spatial arrangement of these stretches is not solved in a significant number of the X-ray structures deposited in the PDB, which also suggests that these loops possess a high degree of conformational flexibility.…”
Section: Resultsmentioning
confidence: 99%
“…Since the ligand‐induced structural alternation is taken into account, ligand–receptor interactions can be better understood by chemometrical analysis. This method has been applied to various analyses of quantitative structure–activity relationships …”
Section: Introductionmentioning
confidence: 99%